Characteristics of pregnancy complicated with type 1 and type 2 diabetes - Misaki Koyama; Mana Taki; Haruko Okamoto; Yosuke Kawamura; Yusuke Ueda; Yoshitsugu Chigusa; Masaki Mandai; Haruta Mogami (Elsevier, 2023)
Objective: Diabetes in pregnancy is a major risk factor for adverse perinatal outcomes such as congenital anomalies, hypertensive disorders of pregnancy (HDP), and macrosomia. For the mechanism of onset of type 1 and type 2 diabetes are different, we focused on the difference in perinatal outcomes between the type 1 and type 2 diabetes groups. Materials and methods: We retrospectively reviewed 22 pregnancies with type 1 diabetes and 15 pregnancies with type 2 diabetes, who were managed in our single center, with regard to maternal diabetes conditions during pregnancy and neonatal birthweight and blood glucose level. Furthermore, we checked the effect of continuous glucose monitoring and continuous subcutaneous insulin injection in pregnancies with type 1 diabetes. Results: Type 1 diabetes in pregnancy was less controllable and increased neonatal birth weight and neonatal hypoglycemia within 2 h after birth after neonatal care unit admission. Continuous glucose monitoring and continuous subcutaneous insulin injection that are convenient to use, had a similar effect in the management of type 1 diabetes during pregnancy, compared with conventional diabetes treatment. In contrast, maternal BMI and HDP were increased in women with type 2 diabetes. Conclusion: In the management of pregnancy with diabetes, we should pay attention to the difference in pregnancy prognosis between type 1 and type 2 diabetes.